The resurrection of Rome - Chesterton, G. K. (Hodder and Stoughton, 1930)
Contents: Part I. The outline of a city; Part II. The story of te Statues; Part III. The pillar of the lateran; Part IV. The return of the Gods; Part V. The return of the Romans; Part VI. The holy island.